An Ethnobotanical Study on the Medicinal Plants of Zarm-rood Rural District of Neka (Mazandaran Province) - A Gholipour; M Ghorbani Nohooji; N Rasuli; M Habibi (Institue of Medicinal Plants, ACECR, 2014)
Background: Medicinal usage of plants is a main part of indigenous people culture which has been formed during centuries in rural area. This knowledge is regarded as a suitable guideline to discovering of novel drugs in modern medicine. Objective: This study has tried to determine and introduce the medicinal plant species, the parts and the way of usage of plants of Zaram-rood in Neka area (North of Iran) using indigenous people questioning. Methods: The flora of the region was studied during the years of 1391 and 1392. At first, the villages and paths were carefully identified by using the appropriate geographical maps and the information was gathered by interviewing with knowledgeable indigenous people. The plant samples were collected from their natural habitats and identified by floristic references. They were deposited in Sari Payame Noor University Herbarium. Results: A total of 64 medicinal plant species belonging to 51 genera and 34 families were collected and identified. The largest families from the viewpoint of species number are Rosaceae and Lamiaceae with 9 and 7 species, respectively. The most medicinal effects were observed in remedy of digestive, blood circulation, and urine excretion system disorders. Amongst identified medicinal plants, 16 species were introduced with new usages. Conclusion: Ethnobotanical knowledge of the area has more remained in old people memory and it is possible to be vanished in later decades. As a result, documenting of this knowledge is necessary. Moreover, there is a good chance to find species with more and useful pharmacological features through ethnobotanical studies.